Work Environment and Teachers’ Job Performance in Basic Schools in Kwara State, Nigeria - Sunday Olaifa, Adeseko; Fajenyo, Ridwan Ayodele; Adeoye, Moses Adeleke; Sagaya, Amdalat Abiodun (Jurnal Pendidikan : Riset dan Konseptual, 2025)
This study was carried out on work environment and teachers’ job performance in basic schools in Kwara state, Nigeria. The study was guided by seven purposes with two research questions and five hypotheses. The research design that was used for this study was a descriptive survey of the correctional-type method. The population of the study consisted of 37,198 teachers in 1580 basic schools in Kwara state. Thirty schools were randomly selected from the state. The sample size involves 330 respondents including teachers and head teachers. The questionnaire was titled Work Environment Teachers’ Job Performance Questionnaire tagged (WETJPQ) and was used by the researcher to elicit information from the concerned respondent. All the research questions were analyzed using descriptive statistics of mean and standard deviation while all research hypotheses were analyzed using inferential statistics of Pearson Product Moment correlation Statistic at 0.05 level of significance. The findings of the study revealed that there is a high level of work environment in basic schools in Kwara state. It was also revealed that there was a significant relationship between work environment and teachers’ job performance in basic schools in Kwara state and there was a significant relationship between school location and teachers’ job performance in basic schools in Kwara state. It was recommended that school administrators should continue to invest in and improve physical facilities, teaching resources, and general working conditions to maintain and further enhance teacher performance.